Determinant Factor of Pamong Praja Police Unit; Evidence from Bogor District, West Java, Indonesia - Anwar, Syaiful; Yusnita, Nancy; Sunaryo, Widodo (Eastasouth Institute, 2024)
The objective of this study is to ascertain and examine the direct and indirect impact of organizational culture on employee performance, specifically via the lens of work satisfaction within the Civil Service Police Unit in Bogor Regency. The population in this study was Bogor district Civil Service Police Unit. The number of samples in this study was 232 samples. Data analysis uses path analysis. The research results show that (1) Strengthening organizational culture can improve the performance of civil service police units. (2) Strengthening job satisfaction can improve the performance of civil service police units. (3) Strengthening organizational culture can increase job satisfaction. (4) The performance of a civil service police unit is positively influenced by its organizational culture. The work happiness variable serves as an efficient mediator between organizational culture factors and employee performance variables. Strengthening both organizational culture and job satisfaction can enhance the performance of civil service police units.